NANOCATALYST IN CHEMISTRY FROM SYNTHESIS TO INDUSTRIAL APPLICATIONS (The Research of Medical Science Review, 2025)
Nanocatalysis has emerged as a transformative field in chemistry, offering enhanced efficiency, selectivity, and sustainability in a wide range of chemical processes. This review focuses on nanocatalysts, examining their synthesis, mechanisms, and industrial applications. The ability to tailor the size, shape, and surface properties of nanocatalysts provides unique advantages over traditional catalysts, enabling faster reaction rates and higher selectivity for specific reactions. The synthesis of Nanocatalysts can be achieved through top-down and bottom-up methods, with approaches such as chemical vapor deposition, sol-gel processes, and green synthesis gaining significant attention for their eco-friendly nature. Characterization techniques like TEM, XPS, and BET analysis allow for the detailed study of Nanocatalyst morphology, surface area, and catalytic activity. The review explores how Nano catalysts function, particularly focusing on their surface effects, interaction with reactants, and the influence of their nanostructure on catalytic performance. Nanocatalysts have found widespread applications in diverse industrial sectors, including energy production, environmental remediation, and the pharmaceutical industry. They play a crucial role in green chemistry, such as in CO2 reduction, wastewater treatment, and biofuel production. Additionally, nanocatalysts are integral to the synthesis of fine chemicals, enhancing the efficiency of reactions used in pharmaceuticals, polymers, and agrochemicals. Despite their promising applications, challenges remain regarding scalability, cost, recyclability, and environmental impact. However, advancements in nanocatalyst design and emerging technologies are paving the way for more sustainable and effective industrial processes. This review highlights the critical role of nanocatalysts in shaping the future of chemical industries.